Analisis Faktor Risiko yang Berhubungan dengan Kejadian Katarak Senilis Di RSU Bahteramas Tahun 2016 - Miranty Aditya Hadini; Amiruddin Eso; Satrio Wicaksono (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2016)
Cataract is a condition where the lens of eyes that normally clear and transparent becomes cloudy. Cataract can cause blindness. Some risk factors related to cataract likes age, sex, diabetes mellitus, UV radiation, smoking and jobs. Some researches argue that these risk factors influence the number of cataracts incidence. This study aims to know the risk factors associated with the incidence of cataracts in Ophtalmology Department in RSU Bahteramas.This study was an analytic observational that used case-control study design. The sample size of this study was 140 respondents consisted of 70 cases and 70 controls were taken by purposive sampling. The data collection was obtained from medical records of patients to determine the age, sex, and history of diabetes mellitus. The instrument of this study was questionnaire to determine their job, education, income and smoking history. Data was declared significant if OR>1.The result of this study has shown that age ≥45 years (OR = 14,397), gender (OR=4.354), history of diabetes mellitus (OR = 10.688), the location of worker (OR = 2.935), education level (OR = 3.842), income (OR = 2.252), and smoking history (OR = 2.771) are risk factors that influence the incidence of senile cataracts.It can be concluded that age, gender, history of diabetes mellitus, outside location worker, low education level, low income, and history of smoking are risk factors for the incidence of senile cataract in RSU Bahteramas Kendari. Keywords :cataract, risk factors, age, gender, history of diabetes mellitus, location of worker, education, income, smoking history.